2007
DOI: 10.1111/j.1525-1446.2007.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Older Adults Regarding Evacuation in the Event of a Natural Disaster

Abstract: Trust and belief in county officials and the media were the best predictors of willingness to evacuate. Participants in this study would need assistance with transportation, preparation, and support for serious health problems in order to evacuate. Further study is needed with a larger, more representative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 9 publications
3
46
0
Order By: Relevance
“…Affiliative behaviour was clearly observable during the 1993 World Trade Centre (WTC) bombings 12 (Aguirre, Wenger, and Vigo 1998) and the evacuation of New Orleans prior to Hurricane Katrina (Rosenkoetter et al 2007). During the 1993 bombings over 75% of those surveyed indicated that they knew something serious had occurred but only 8.7% of the groups surveyed chose to act and evacuate.…”
Section: Panic or Fight Flight And Affiliatementioning
confidence: 99%
“…Affiliative behaviour was clearly observable during the 1993 World Trade Centre (WTC) bombings 12 (Aguirre, Wenger, and Vigo 1998) and the evacuation of New Orleans prior to Hurricane Katrina (Rosenkoetter et al 2007). During the 1993 bombings over 75% of those surveyed indicated that they knew something serious had occurred but only 8.7% of the groups surveyed chose to act and evacuate.…”
Section: Panic or Fight Flight And Affiliatementioning
confidence: 99%
“…On the other hand, following disasters, some pre-existing medical problems may be aggravated (25,31,38,42,48).…”
Section: Pre-existing Medical Needsmentioning
confidence: 99%
“…The findings of some studies showed that chronic diseases may interfere with older people's ability to evacuate; for example, somebody with the chronic obstructive pulmonary disease (COPD) who is trying to go down the stairs may face difficulty in evacuating (32,33,38,42). Moreover, chronic diseases can interfere with access to services after disasters; for example, a person with arthritis may have problems standing in line for access to services (32).…”
Section: Pre-existing Medical Needsmentioning
confidence: 99%
“…Studies in context of Hurricane Katrina revealed that elderly people needed assistance with transportation, preparation, and support for serious health problems, as well as anticipatory emergency plan that includes a kit of essential medical supplies and information, important contact information, and relocation sites in order to evacuate (Rosenkoetter, Covan, Cobb, Bunting, & Weinrich, 2007). Moreover, frail elders with serious physical, cognitive, economic, and psychosocial challenges, utilize most of their functional reserve on daily survival, dealing with health conditions, economic constraints, social isolation, and impaired mobility, as a result, they are likely to have difficulty coping with additional stress and subsequently may be even more adversely affected by disasters than the general population (Pekovic et al, 2007).…”
Section: Elderly Peoplementioning
confidence: 99%